EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI): development of a consensus patient index for primary Sjögren's syndrome. Issue 6 (22nd February 2011) - Seror, Raphaèle; Ravaud, Philippe; Mariette, Xavier; Bootsma, Hendrika; Theander, Elke; Hansen, Arne; Ramos-Casals, Manel; Dörner, Thomas; Bombardieri, Stefano; Hachulla, Eric; Brun, Johan G; Kruize, Aike A; et al.
Abstract : Objectives: To develop a score for assessment of patients' symptoms in primary Sjögren's syndrome (SS): the EULAR SS Patient Reported Index (ESSPRI). Methods: Dryness, pain, somatic and mental fatigue were identified as the main symptoms of patients with primary SS, in studies developing the Profile of Fatigue and Discomfort (PROFAD) and Sicca Symptoms Inventory (SSI). It was suspected that a single 0–10 numerical scale for each domain was sufficient to assess these symptoms. These four scales were gathered to form the ESSPRI. 230 patients, from 12 countries completed the ESSPRI, SSI and PROFAD questionnaires and a 0–10 patient global assessment (PGA). Correlations between each symptom and PGA were obtained. Multiple regression modelling, using PGA as 'gold standard' was used to select domains and estimate their weights. Results: PGA had good correlation with dryness, limb pain, fatigue and mental fatigue (r=0.49–0.59, all p<0.0001), but correlated less well with individual dryness features. In multivariate analysis, dryness, limb pain and fatigue, but not mental fatigue, were significantly associated with PGA; weights derived from the regression were identical for these three domains. Thus, ESSPRI was redefined as the mean of the three scales: dryness, limb pain and fatigue. Lastly, ESSPRI significantly correlated with PGA (r=0.70), PROFAD (r=0.73) and SSI (r=0.66). Conclusion: ESSPRI is a very simple index designed to measure patients' symptoms in primary SS. It has good construct validity and is well correlated with SSI and PROFAD. ESSPRI should now be validated for use as an outcome measure in clinical trials.